Lossless Data Hiding Based on Adjacency Pixel Differences - Lakshmanan, S; Rani, Mary Shanthi (International Journal of Computer Sciences and Engineering, 2018)
Image steganography has become a vibrant research area due to increase in digital image transmission over untrusted network. Generally, after recovering the hidden data from a stego image, the host image data cannot be reconstructed perfectly. This is a main challenge for applications demanding lossless host image recovery. In this paper, a new lossless reversible data hiding technique is proposed based on differences of adjacent pixels for embedding data and has more hiding capacity compared to existing methods. The number of hiding bits that can be embedded into an image equals the number of pixels related with the peak point. The performance of the algorithm has been evaluated with hiding capacity and peak signal to noise ratio (dB). The experimental results show that the host image and hidden information can be exactly retrieved from the stego image.